Exercise, sports and musculoskeletal medicine in UK medical school curricula: a survey. Issue 2 (20th January 2011) - Oluwajana, F; Rufford, C; Morrissey, D
Abstract : Introduction: Exercise and obesity (EO) and sports and exercise medicine (SEM) are important topics in today's society and musculoskeletal medicine (MSK) is already a well established subject in medical schools. Despite the importance of these subjects, little is known about their occurrence in medical school curricula. the study aimed to investigate the availability of EO, SEM and MSK teaching in UK medical schools, opinions regarding the importance and quality of the teaching and to compare SEM and EO with MSK teaching. Method: An anonymous online survey was designed, piloted and distributed to the deans of undergraduate medical education at 33 UK medical schools. reminder emails were sent to participants every 4 weeks for 4 months. Results: The response rate was 76%. all medical schools have a direct focus on MSK in their curriculum. 68% have a direct focus on EO and 40% on SEM. There are more optional study opportunities in msk. 92% of medical schools assess MSK knowledge, while only 60% and 28% do so for EO and SEM respectively. MSK is perceived to be more important and have better quality teaching. The most common barrier to improving education was space in the curriculum. Conclusions: EO and SEM teaching are uncommon and considered less important in UK medical schools compared to MSK teaching. Increasing the perceived importance of these subjects and providing curricular guidance to medical schools will help improvements to be implemented. The optional curriculum is likely to be the most appropriate initial method of increasing and improving teaching in EO and SEM.